PENGARUH COINCIDENT ECONOMIC INDICATOR DAN LEADING ECONOMIC INDICATOR TERHADAP RETURN SAHAM (Studi terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia periode 2003-2011) - Sumartini, Ade; Denny, Erman (Faculty of Economics and Business Diponegoro University, 2012)
The research looked at the influence of Coincident Economic Index and Leading Economic Index besed on Business cycle theory for the period of JCI stock returns from 2003 to 2011. The variables used are issued by the Danareksa Institute variables to form the Coincident Economic Index (CEI) and the Leading Economic Index (LEI). Coincident Economic Index is used to determine a country's current economic conditions and the Leading Economic Index is used to predict economic conditions in the future. CEI variables used are retail sales, consumption of cement, the money supply and car sales. While the LEI variable used was the arrival of foreign tourists, exports and consumer price index. This research using multiple regression with SPSS program.